ANALISIS KINERJA KEUANGAN BANK MANDIRI KONVENSIONAL DAN BANK MANDIRI SYARIAH CABANG SANGATTA - Putri, Cut Emylia (EKONOMIA, 2018)
This research is conducted at PT. Bank Syariah Mandiri and PT. Bank Mandiri, (conventional bank) in which the development of syariah banks are increasing rapidly in recent years encourage authors to conduct research on the performance of the bank and know which of the two who have better financial performance. This study aims to know and analyze how the financial performance of both banks based on capital aspect using CAR (Capital Adequacy Ratio) ratio, earning asset quality aspect using NPL (Non Performing Loan) ratio, rentability aspect using ROA (Return On Assets) using the ratio of BOPO (Operating Expense to Operating Income), the fund speculation using LDR (Loan to Deposit Ratio) ratio.Method’s used in this study is the method of documentation and observation. Data collected is a general overview of companies, organizational systems and Financial Report field by using Likert scale. The method of analysis used in conducting the research is by using the Independent Sample T-Test. Based on the results of research that has been done at PT. Bank Mandiri and Bank Syariah Mandiri, the analysis of financial performance derived from the ratio of CAR, NPL, ROA, BOPO, LDR indicates that there is a significant difference between the performance of syariah banking compared with conventional banking when viewed from the mean of bank performance as a whole represented by variable